The Dynamics of Creative Ideation: Introducing a New Assessment Paradigm - Barbot, Baptiste (Frontiers in Psychology, 2018)
Despite six decades of creative cognition research, measures of creative ideation have heavily relied on divergent thinking tasks, which still suffer from conceptual, design and psychometric shortcomings. These shortcomings have greatly impeded the accurate study of creative ideation, its dynamics, development, and integration as part of a comprehensive psychological assessment. After a brief overview of the historical and current anchoring of creative ideation measurement, overlooked challenges in its most common operationalization (i.e., divergent thinking tasks framework) are discussed. They include (1) the reliance on a single stimulus as a starting point of the creative ideation process (stimulus-dependency), (2) the analysis of response quality based on a varying number of observations across test-takers (fluency-dependency), and (3) the production of “static” cumulative performance indicators. Inspired from an emerging line of work from the field of cognitive neuroscience of creativity, this paper introduces a new assessment framework referred to as “Multi-Trial Creative Ideation” (MTCI). This framework shifts the current measurement paradigm by (1) offering a variety of stimuli presented in a well-defined set of ideation “trials”, (2) reinterprets the concept of ideational fluency using a time-analysis of idea generation and (3) captures individual dynamics in the ideation process (e.g., modeling the effort-time required to reach a response of maximal uncommonness) while controlling for stimulus-specific sources of variation. Advantages of the MTCI framework over the classic divergent thinking paradigm are discussed in light of current directions in the field of creativity research.